Criss-Cross Mo Chara - Mac Lochlainn, Gearóid,Braidner, Mark (Cló lar-Chonnacht, 2011)
A bilingual collection of poetry by the Belfast poet, Gearóid Mac Lochlainn including a CD (print version only) featuring the poet reading from the collection to music adapted by the blues musician, Mark Braidner, for this recording.
Description based on publisher supplied metadata and other sources